Gobiesox lanceolatus, a new species of clingfish (Teleostei: Gobiesocidae) from Los Frailes submarine canyon, Gulf of California, Mexico - Hastings, Philip A.; Conway, Kevin W. (Zootaxa, 2017)
Gobiesox lanceolatus is described from a single specimen collected from 300 meters depth in the Los Frailes submarine canyon in the southwestern Gulf of California. The "Canyon Clingfish" is unique within Gobiesox in having a lanceolate caudal fin, with the central rays longer than those above and below them. It is also distinguished by 14 dorsal-fin rays (first tiny and unsegmented), 11 anal-fin rays, 28 pectoral-fin rays, anus slightly closer to anal-fin origin than to posterior margin of pelvic disc, and dorsal-fin origin in front of vertical from anus. It is most similar to Gobiesox eugrammus, known from Isla Guadelupe, the coast of outer Baja California and southern California. This is the deepest record for a species of Gobiesox and only four other species of clingfishes are known from greater depths.